Prognostic value of Mastora obstruction score in acute pulmonary embolism - Račkauskienė, Jolita; Gedvilaitė, Vaida; Matačiūnas, Mindaugas; Abrutytė, Mažvilė; Danila, Edvardas (Acta medica Lituanica, 2020)
Background. To evaluate the clinical significance of Mastora obstruction score in hemodynamically stable patients with acute pulmonary embolism (aPE). Materials and methods. One-hundred-and-six patients with newly diagnosed aPE, confirmed by computed tomography pulmonary angiography (CTPA), were included in the study and prospectively examined. aPE severity was assessed by using Mastora obstruction score. According to the Mastora index, patients were divided into “non-massive” and “massive” groups. The patients’ medical histories and blood laboratory data were collected, and instrumental tests were performed and analyzed. Results. Eighty-two (77%) of the patients had “non-massive” aPE. Cough (48%), fever (44%), and pleural effusion (48%) occurred significantly more often in the “non-massive” PE group, while syncope (42%) and right ventricular dysfunction (86%) were more frequent in the “massive” PE group. The probability of the right ventricular dysfunction was significantly higher in the presence of increased pulmonary artery pressure (Cramer’s V = 0.410; p < 0.0001) and respiratory failure (Cramer’s V = 0.247; p = 0.032). Increased CRP level was found in the majority of the patients (90%). D-dimer level